Karakteristik Model Quantum Learning Dalam PAUD - Ahmad Zain Sarnoto; Ely Budiyanti (UIN Sultan Maulana Hasanudin Banten, 2021)
This study explores the characteristics of Quantum Learning in early childhood education institutions that are characterized by Islam. The main elements of Qurantum are oriented towards the growth and development of active and participatory learners. The role of early childhood teachers is more as a mentor or facilitator, and not a presenter of universal science, because in the qurantum, knowledge cannot be transferred from teacher to child without the child's own activity. Therefore, teachers need to know in advance how children think, develop and appreciate children's experiences and thinking patterns, by using a variety of learning methods that allow children to actively construct knowledge. Qualitatively descriptive, this research was conducted by taking the research location in RA Bait Qur'any at-Tafkir Tangerang Selatan. It can be concluded that his main character rests on the formation of the Islamic personality. Two patterns are used, namely aqliyah and nafsiyah. The Aqliyah approach is the process of linking facts to tsabiqoh edicts. The Nafsiyah approach is that the teacher acts as a mother, that is, giving sacrificial love, conveying the hopes and souls of the teacher with the students unifying.